Do body-worn cameras reduce disparities in police behavior in minority communities?: evidence of nuanced influences across Black and Hispanic neighborhoods - Huff, Jessica (Criminology & public policy, 2022)
Research Summary The adoption of body-worn cameras (BWCs) is often promoted in response to contentious police use of force incidents involving minority civilians. BWCs are expected to improve policing outcomes by enhancing accountability, although researchers have yet to determine whether BWCs can reduce racial/ethnic disparities. I examine whether BWCs mitigate the influence of neighborhood racial/ethnic context on arrests and use of force using cross-classified logistic regression models to examine the outcomes of 900,000+ police-civilian contacts in Phoenix. Arrests were significantly more likely to occur in Hispanic and Black neighborhoods before and after BWC deployment, even accounting for situational, officer, and neighborhood characteristics. When BWCs were activated in Black neighborhoods, the odds of arrest decreased by 38%. However, BWCs did not moderate the influence of neighborhood percentage of Hispanic on arrest. The neighborhood racial/ethnic context was not associated with the use of force pre- or post-BWC deployment. Policy Implications Although BWCs have been associated with several positive outcomes, their ability to reduce racial/ethnic disparities appears to be overstated. As such, more targeted approaches to reducing disparities in policing outcomes are needed. For example, leveraging the information collected through BWCs could facilitate enhanced supervision to identify officers engaging in racially disparate practices and hold them accountable. Although neighborhood racial/ethnic context was a robust predictor of arrest, these results point to nuanced influences of BWC activation in minority communities. This could be due to differential causes of arrest in Black and Hispanic neighborhoods.